Analysis of sorption efficiency of activated carbon for removal of anthracene and pyrene for wastewater treatment. Issue 1 (2nd January 2016) - Rasheed, Anjum; Farooq, Farah; Rafique, Uzaira; Nasreen, Saima; Aqeel Ashraf, Muhammad
Abstract: The potential carcinogenicity and mutagenicity has placed polycyclic aromatic hydrocarbons (PAHs) on top priority calling for immediate management strategies. The present study draws its rationale that industries should opt for sustainable and economically viable solutions. The powdered activated carbon (PAC) is applied as adsorbent for removal of anthracene and pyrene under ambient conditions. Aliquot of batch run on GC–MS demonstrated progressively increasing percentage removal of anthracene and pyrene with increase in time. Further, pyrene shows a slower but regular increase in adsorption with distinct equilibrium at 100 min. However, anthracene depicts simultaneous adsorption–desorption pattern with multiple equilibriums. This suggests that pyrene is more stable due to its higher molecular weight and boiling point resisting its diffusion into adsorbent. The maximum removal of >99% is achieved after contact of 4 h between adsorbate and adsorbent. The fitness of pseudo-first-order kinetics suggests the linear and direct relationship of pyrene with time. Furthermore, the agreement of experimental data to Elovich model proposes chemisorption as the preferred mode of action for removal of PAHs on the surface of PAC. The study concludes that activated carbon is a successful alternate for efficient removal of PAHs from wastewater. Therefore, it can be adapted by industries as a sustainable remediation.